Biomedical Informatics and Technology First International Conference, ACBIT 2013, Aizu-Wakamatsu, Japan, September 16-17, 2013. Revised Selected Papers - Pham, Tuan D.; Ichikawa, Kazuhisha; Oyama-Higa, Mayumi; Coomans, Danny; Jiang, Xiaoyi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the First International Conference on Biomedical Informatics and Technology, ACBIT 2013, held in Aizu-Wakamatsu, Japan, in September 2013. The ??? revised full papers presented together with 14 keynotes and invited talks were carefully reviewed and selected from 48 submissions. The papers address important problems in medicine, biology and health using image analysis, computer vision, pattern analysis and classification, information visualization, signal processing, control theory, information theory, statistical analysis, information fusion, numerical analysis, fractals and chaos, optimization, simulation and modeling, parallel computing, computational intelligence methods, machine learning, data mining, decision support systems, database integration and management, cognitive modeling, and applied linguistics.
Medicine, biology and health using image analysis -- Computer vision, pattern analysis and classification -- Information visualization -- Signal processing -- Control theory -- Information theory -- Statistical analysis -- Information fusion -- Numerical analysis -- Fractals and chaos -- Optimization -- Simulation and modeling -- Parallel computing -- Computational intelligence methods -- Machine learning -- Data mining -- Decision support systems -- Database integration and management -- Cognitive modeling -- Applied linguistics.
Keywords: Computer science; Health informatics; Image processing; Pattern recognition; Application software; Computer Science; Health Informatics; Pattern Recognition; Image Processing and Computer Vision; Computer Applications; Electronic books